Thermal conductivity of confined-water in graphene nanochannels. (May 2020) - Zhao, Zhixiang; Sun, Chengzhen; Zhou, Runfeng
Highlights: Thermal conductivity of water confined in the graphene nanochannels is studied by equilibrium molecular dynamics simulations. Thermal conductivity of confined water is anisotropic owing to the weakened/strengthened molecular collisions. Thermal conductivity has a great dependence on the channel height due to the varying contribution of potential wells. Abstract : Transport properties of nano-confined fluids present distinctive characteristics comparing to the bulk fluids owing to the confinements and the additional fluid-solid interactions. Here, the thermal conductivity of water confined in the graphene nanochannels is calculated by equilibrium molecular dynamics simulations with the Green-Kubo formula. The results show that the thermal conductivity of nano-confined water is obvious anisotropic, i.e. the perpendicular thermal conductivity is obviously lower than the longitudinal thermal conductivity. This anisotropic thermal conductivity is caused by the inhibited molecular collisions in the perpendicular direction but the enhanced collisions in the longitudinal direction because of the trap of water molecules in the potential wells near the graphene walls. With increasing the channel height, the contributions of the trapped water molecules on the inhibited thermal conductivity in the perpendicular direction and the enhanced thermal conductivity in the longitudinal direction are both weakened, such that the thermal conductivity in the three directions all approach to their bulk values. In summary, the anisotropy and size-dependence of the thermal conductivity of confined water in graphene nanochannels are identified and the underlying mechanisms are revealed from the insights of thermodynamic physics. Graphical abstract: Image, graphical abstract